Identifying students’ knowledge of multimedia technology use in secondary education learning - Paulo Alves Cabral; Kristiani Kristiani; Pedro Correia (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2026)
This study presents an analysis of students’ knowledge regarding multimedia technology as a subject within the teaching and learning process, particularly in the context of practical laboratory sessions. The research is entitled Identification of Students’ Knowledge of Multimedia Technology Use in Secondary Education Learning. The objectives of this study are to examine the importance of multimedia technology in secondary education and to identify how multimedia technology is utilized by students in the teaching and learning process at the secondary level. The population of this study consisted of twenty (20) schools, while the sample included five (5) representative schools, involving a total of 50 students, comprising 28 male and 22 female students. This study employed a qualitative descriptive method, and the data collection techniques used were documentation and questionnaire-based surveys. The primary instrument for data collection was a structured questionnaire. The results of the study indicate that out of the 50 secondary school students from five schools, all respondents acknowledged that multimedia technology is a subject included within their learning context. Regarding familiarity with multimedia technology topics, 66% of students responded “yes,” while 34% responded “no,” indicating that the majority of students possess knowledge of multimedia technology. However, concerning the availability of practical laboratory sessions related to multimedia technology, only 36% of students responded “yes,” while 64% responded “no,” suggesting that most students still lack access to practical laboratory facilities. Furthermore, regarding the use of materials in practical sessions related to operating computer programs, only 10% of students responded “yes,” while 80% responded “no.” These findings indicate that only a small proportion of students understand the process of operating computer programs.